'BLEARY EYES AND DROOPING EARS': IMAGES OF THE BODY AND SELF‐REPRESENTATION IN HORACE SERMONES BOOK ONE. (December 2014) - FREEMAN, ROD
<x xml:space="preserve">Abstract</x> In this article I consider the literary programme that Horace establishes in Sermones 1 and then discuss in two subsequent sections the implications of this programme for our understanding of various themes, associated with Augustan ideology, that run through this text. By re‐evaluating persona theory and evidence for audience reactions to pseudo‐biographical writing in the Ancient world, I assimilate the purely 'textual' approach with the broader ethical, political and social questions which the text raises, and consider how the symbolic and intertextual properties of images of the body in the text, and issues of self‐representation, allow for diverse readings of his work, reconciling the hitherto separated literary Callimachean poet with the quasi‐biographical 'Horace'.